Africa: War and Conflict in the Twentieth Century - Stapleton, Tim, author.
1 online resource
Keywords: "This book examines the causes, course and consequences of warfare in twentieth century Africa, a period which spanned colonial rebellions, both World Wars, and the decolonization process. Timothy Stapleton contextualizes the essential debates and controversies surrounding African conflict in the twentieth century while providing insightful introductions to such conflicts as; African rebellions against colonial regimes in the early twentieth century, including the rebellion and infamous genocide of the Herero and Nama people in present-day NamibiaThe African fronts of World War I and World War II, and the involvement of colonized African peoples in these global conflictsConflict surrounding the widespread decolonization of Africa in the 1950s and 1960sRebellion and civil war in Africa during the Cold War, when American and Soviet elements often intervened in efforts to turn African battlegrounds into Cold War proxy conflictsThe Second Congo Civil War, which is arguably the bloodiest conflict in any region since World War II. Supported by a glossary, a whos who of key figures, a timeline of major events, a rich bibliography, and a set of documents which highlight the themes of the book, Africa: War and Conflict in the Twentieth Century is the best available resource for students and scholars seeking an introduction to violent conflict in recent African history. "--Provided by publisher.